"It's the Teacher's Responsibility:" Examining Pre-service and In-service Teachers' Responses to Racial Discrimination. Issue 2 (3rd April 2023) - Baker, Blair A.; Davis, Summer; Wilkins-Yel, Kerrie G.; Mukherjee, Atrayee; Paneto, Adrian
ABSTRACT: In K-12 settings, misunderstandings of racial dynamics and color-blind attitudes may stymie teachers from adequately addressing racial discrimination amongst students. This study qualitatively asked if, why, and how pre- and in-service teachers would hypothetically intervene on racial discrimination toward a Black student, and whether color-blind racial attitudes in teachers manifest in their intervention approaches. Findings suggest pre- and in-service educators intend to intervene on racial discrimination. However, the rationale and strategies for intervening often reflect color-blind or biased racial attitudes, suggesting the need for consultation professionals to support teachers in implementing more effective intervention strategies. Given the racial nature of this consultation need, the authors present the multicultural consultation framework as a potentially useful lens through which consultants can work with educators on discrimination intervention.